Pore‐water exchange driven by tidal pumping causes alkalinity export in two intertidal inlets - Peter A. Faber; Victor Evrard; Ryan J. Woodland; Ian C. Cartwright; Perran L. M. Cook (Limnology and Oceanography, 2014)
Carbon (C) and alkalinity export from two adjacent intertidal inlets with different terrestrial inputs was investigated. One inlet receives a small creek from an agriculturally dominated catchment, leading to the input of terrestrially sourced material, whereas the other is relatively isolated from terrestrial inputs. Using time‐series measurements, we calculated the total advective exchange of dissolved organic C (DOC; 0–25 mmol m ‒2 d ‒1 ), dissolved inorganic C (DIC; 130–450 mmol m ‒2 d ‒1 ), total alkalinity (TA; 46–310 mmol m ‒ d ‒1 ), and the nutrients nitrate (1.0–1.1 mmol m ‒2 d ‒1 ), ammonia (0.0043–0.10 mmol m ‒2 d ‒1 ), and phosphorus (0.016–0.25 mmol m ‒2 d ‒1 ). Radon‐222 ( 222 Rn) data indicated that pore‐water exchange played an important part in controlling C export from the sediment as an advective flux. The residence time of pore water within both inlets was ~ 6.6–7.4 h, indicating that pore‐water exchange is driven by tidal pumping. The inlet with the greater amount of terrestrial inputs exported much more TA (310 vs. 46 mmol m ‒2 d ‒1 ), suggesting that the extent of land‐to‐sea connectivity influences how C is exported. We hypothesize that this is due to the increased input of iron (Fe) from terrestrial sources, which fosters net TA production through the burial of reduced sulfur species as Fe sulfides. A simple mass balance showed that the TA fluxes observed over 24 h were higher than could be sustained continuously with Fe input from the catchment (0.49 mmol Fe m ‒2 d ‒1 ), meaning that the observed TA fluxes could not be sustained on long timescales. It is most likely that there are periods of net reduction and net oxidation in response to wave action and calm conditions, highlighting the importance of long‐term monitoring over different seasons and weather patterns to obtain representative budgets.